Determination of Generalized Inertial Forces in Relative Motion of Mechanical Systems of a Railway-Vehicle Type - Kisilowski, J.; Zboiński, K. (Engineering Transactions, 1989)
Comparing with what is known from the literary sources, this paper presents a simpler method of determining the inertial forces which result from the relative motion for the mechanical systems consisting of many rigid bodies with holonomic and nonholonomic constraints. The method is based on a theorem, the proof of which will be included in this work. Although the presented method has been worked out primarily to meet the need of modelling railway vehicle vibrations, for which the assumptions of the theorem are easily satisfiable, it can also be applied to any mechanical system satisfying the mentioned assumptions.